Long‐term ozone changes and associated climate impacts in CMIP5 simulations. Issue 10 (30th May 2013) - Eyring, V.; Arblaster, J. M.; Cionni, I.; Sedláček, J.; Perlwitz, J.; Young, P. J.; Bekki, S.; Bergmann, D.; Cameron‐Smith, P.; Collins, W. J.; Faluvegi, G.; Gottschaldt, K.‐D.; et al.
Abstract: [1] Ozone changes and associated climate impacts in the Coupled Model Intercomparison Project Phase 5 (CMIP5) simulations are analyzed over the historical (1960–2005) and future (2006–2100) period under four Representative Concentration Pathways (RCP). In contrast to CMIP3, where half of the models prescribed constant stratospheric ozone, CMIP5 models all consider past ozone depletion and future ozone recovery. Multimodel mean climatologies and long‐term changes in total and tropospheric column ozone calculated from CMIP5 models with either interactive or prescribed ozone are in reasonable agreement with observations. However, some large deviations from observations exist for individual models with interactive chemistry, and these models are excluded in the projections. Stratospheric ozone projections forced with a single halogen, but four greenhouse gas (GHG) scenarios show largest differences in the northern midlatitudes and in the Arctic in spring (~20 and 40 Dobson units (DU) by 2100, respectively). By 2050, these differences are much smaller and negligible over Antarctica in austral spring. Differences in future tropospheric column ozone are mainly caused by differences in methane concentrations and stratospheric input, leading to ~10 DU increases compared to 2000 in RCP 8.5. Large variations in stratospheric ozone particularly in CMIP5 models with interactive chemistry drive correspondingly large variations in lower stratospheric temperature trends. The results also illustrate that future Southern Hemisphere summertime circulation changes are controlled by both the ozone recovery rate and the rate of GHG increases, emphasizing the importance of simulating and taking into account ozone forcings when examining future climate projections. Key Points: CMIP5 models all consider past ozone depletion and future ozone recovery Multimodel ozone agrees well with observations but individual models deviate Future climate is sensitive to rates of both ozone recovery and GHG increases